Analisis efektifitas penerapan perencanaan pajak untuk meminimalkan beban pajak perusahaan (Studi pada PT Andalan Bisturi Pratama) - Maula Rofita; Saman Saman (University of Merdeka Malang, 2021)
This study aims to evaluate whether the application of taxation has been implemented effectively and can minimize the tax burden. Data collection techniques were carried out by means of interviews and documentation. The analysis used is quantitative. From the results of the study, it was found that the application of tax planning carried out by the company was not effective because in the recognition of costs it was still using the accounting basis and not in accordance with the tax law.